Procedimientos actualizados para la no revictimización por violencia sexual - Armijos Fernández, Kathia Julissa (Machala : Universidad Técnica de Machala, 2022)
Introduction: One in three women suffers or has suffered from physical or sexual violence before reaching the age of majority, according to the United Nations Organization (UN) and the World Health Organization (WHO), at the national level 65 of every 100 women has experienced some type of violence and according to UNICEF Ecuador, one in four girls and one in six boys has been sexually violated, these crimes exposed to justice, subjects the victims to testify reliving the fact and the present work seeks processes that reduce re-victimization. Development: In Sweden the victim has more than the lawyer, a målsägandebiträde, this person has more than legal knowledge, serves as support. Any sexually assaulted person can apply to the National Authority for compensation in respect of any injury, physical or mental impairment, loss or damage to property in Sri Lanka. The involvement of dream processes within the so-called anti-violence centers in Italy; Software such as iERT which is divided into 5 sessions or digital evidence must contain a standardized process and the language of sexual abuse based on images is proposed. Conclusions: The best way to avoid or minimize re-victimization would be to avoid its cause, however, since this cannot be controlled, there are currently promising measures, where technology such as iERT software and even standardized protocols for interrogation of minors are involved. of age or support lawyers.
Introducción: Una de cada tres mujeres sufre o ha sufrido de violencia física o sexual antes de cumplir la mayoría de edad, según la Organización de Naciones Unidas (ONU) y la Organización Mundial de la Salud (OMS), en el ámbito nacional 65 de cada 100 mujeres ha experimentado algún tipo de violencia y según UNICEF Ecuador, una de cada cuatro niñas y uno de cada seis niños ha sido violentado sexualmente, estos delitos expuestos ante la justicia, somete a las víctimas a testificar reviviendo el hecho y el presente trabajo busca procesos que disminuyan la revictimización. Desarrollo: En Suecia la víctima posea a más del abogado, un målsägandebiträde, esta persona a más de poseer conocimientos jurídicos le sirve de apoyo. Cualquier persona agredida sexualmente puede presentar una solicitud a la Autoridad Nacional solicitando compensación con respecto a cualquier lesión, impedimento físico o mental, pérdida o daño a la propiedad en Sri Lanka. El involucramiento de los procesos oníricos dentro del los denominados centros de antiviolencia en Italia; Un software como iERT el cual se divide en 5 sesiones o la evidencia digital debe contener un proceso estandarizado y se propone el lenguaje del abuso sexual basado en las imágenes.
Keywords: VIOLENCIA SEXUAL; REVICTIMIZACION; ABUSO SEXUAL